THE EVALUATION OF PEER AND CROSS-AGE LEARNING MODEL AT IAIN SURAKARTA (EVALUASI MODEL PEMBELAJARAN PEER DAN CROSS-AGE DI IAIN SURAKARTA) - Umi Pujiyanti; Robith Khoiril Umam (UIN Raden Mas Said Surakarta, 2017)
This article is aimed at describing the differences of tutoring process and the responses of tutees related to the tutors classified as peer and cross age The research underlying this article applies descriptive-qualitative method. The data were obtained from observation, document analysis and interview. The findings show that there are advantages and disadvantages of both models. Peer tutors were more familiar to the tutee. It built better communication and high motivation in the classes. Meanwhile, cross-age tutors tended to be respected by tutee that made them easier in organizing the classes. On the other hand, peer tutors looked less serious and were often ignored by tutees. Similarly, cross-age tutors faced difficulties in preserving their attittudes since they were taken as the models by their tutees.